Studying extreme events: An interdisciplinary review of recent research - J. Alvre; L.H. Broska; D.T.G. Rübbelke; S. Vögele (Heliyon)
While extreme events have been a focus of research for several decades, often centered around the causes and impacts of meteorological and climatological events, the term has expanded into a range of other disciplines, exploring a wide variety of associated topics. Analytical tools and definitions have hereby posed a challenge that has been addressed in different ways. Drawing from a broad body of research on extreme events, this review takes into account the often complex and cascading nature of extreme events in order to provide a large-scale overview of the main themes, discussions and trends of extreme event research. It does so by combining a systematic, large-scale analysis of publications on extreme events from 2019 to 2023 with additional database information on extreme events in the first part and a more in-depth narrative review on the main issues in the second part. The results show that extreme event research is dominated by meteorological and climatological extreme events and publications in the physical and life sciences. Identified focal areas in current research activities on extreme events are discussed in regards to issues of definitions and mathematical comprehension, extreme events and their impact in nature, and the interrelation of extremes and humans, including impacts on humans, extremes in human cognition, and human behaviors as causes and responses to extreme events.